The Doctrine of Excessive Formalism in the Legal Theory and Practice of the European Court of Human Rights - Shcherbaniuk, Oksana; Bohdanevych, Tetiana (Frontiers in Law, 2024)
As a means of organising certain existing disputes and resolving conflicts within society, it has made the institution of procedural formalities necessary since the beginning of history. The existence of formalities in a proceeding, whether judicial or extrajudicial, serves to limit certain situations in the course of the process. It is well known that there are several principles that regulate the formalities of procedure, mainly by establishing procedural limits. These reason values are thus aimed at achieving the principles of purpose. The methodological basis of the article is the dialectical method of cognition based on materialistic dialectic with the use of such general scientific methods as analysis, synthesis, induction, deduction, abstraction, specification, analogy, hypothesis building method, and the system-structural method. The study has resulted in the identification of cases of excessive formalism by courts when applying the rules of procedural law. The practical significance of the results obtained is to prevent such mistakes by law enforcement authorities in the future. As a result of writing this article, the author has established that the main manifestations of excessive formalism are the creation by the court of procedural obstacles to the implementation of procedural rules by the parties to the case, strict interpretation by national legislation of the procedural rules, and return of an administrative claim on formal grounds. It is proved that excessive formalism in resolving the issue of acceptance of a statement of claim leads to a violation of the right to fair judicial protection.